VOCABULARY LEARNING STRATEGIES EMPLOYED BY POSTGRADUATE STUDENTS OF MATARAM UNIVERSITY IN ACADEMIC YEAR 2014/2015 - Ida Nyoman Tri Darma Putra (Jo-ELT (Journal of English Language Teaching) Fakultas Pendidikan Bahasa & Seni Prodi Pendidikan Bahasa Inggris IKIP, 2015)
Vocabulary is crucial to language learning in which lack vocabulary knowledge will make learner difficult to learn the language. Vocabulary knowledge is affected by the vocabulary learning strategies. The purpose of the present study was to identify the vocabulary learning strategies employed by postgraduate students and also try to explore the most and least vocabulary strategy used by Mataram university postgraduate students. The sample of this study was 40 postgraduate students of English department in FKIP Mataram University in academic year 2014/2015. Vocabulary learning strategies questionnaire was used in this study to identify students’ frequency of vocabulary learning strategies use. The result of the study showed that the research subjects used the vocabulary learning strategies in all five categories. The memory strategies (37.80) were the most frequently strategies by all subjects. Meanwhile determination strategies (mean=19.43) were determined as the second frequently used strategies followed by cognitive (mean=15.23), metacognitive (mean=13,26). The social strategies were determined as the least used strategies by all students with mean score of 11.00. In specific, looking at each item of category, the most vocabulary learning strategy used by postgraduate students was guessing from context (mean=3.33) which is part of determination category and the least vocabulary learning strategy used by postgraduate students was ask other people to discover the meaning of new vocabulary (mean=1.50)